2006
DOI: 10.1016/j.febslet.2006.05.069
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the cytochrome P450 enzymes responsible for the ω‐hydroxylation of phytanic acid

Abstract: Patients suffering from Refsum disease have a defect in the a-oxidation pathway which results in the accumulation of phytanic acid in plasma and tissues. Our previous studies have shown that phytanic acid is also a substrate for the x-oxidation pathway. With the use of specific inhibitors we now show that members of the cytochrome P450 (CYP450) family 4 class are responsible for phytanic acid x-hydroxylation. Incubations with microsomes containing human recombinant CYP450s (Supersomes TM ) revealed that multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Antibody inhibition experiments (13,14) suggest that P450 4F2/4F3B in human liver and kidney microsomes contribute ϳ66% to the formation of 20-HETE. Recently, P450s 4F2 and 4F3B were found to -hydroxylate very long chain saturated fatty acids (15) as well as phytanic acid (16). Our preliminary experiments using com-mercially available Supersomes TM (BD Gentest) indicate that P450 4F2 also -hydroxylates oleic acid, stearic acid, and palmitic acid, but not lauric acid.…”
mentioning
confidence: 98%
“…Antibody inhibition experiments (13,14) suggest that P450 4F2/4F3B in human liver and kidney microsomes contribute ϳ66% to the formation of 20-HETE. Recently, P450s 4F2 and 4F3B were found to -hydroxylate very long chain saturated fatty acids (15) as well as phytanic acid (16). Our preliminary experiments using com-mercially available Supersomes TM (BD Gentest) indicate that P450 4F2 also -hydroxylates oleic acid, stearic acid, and palmitic acid, but not lauric acid.…”
mentioning
confidence: 98%
“…This phenomenon is thought to reflect the role of P450 4F2 in hepatic clearance of vitamin K (McDonald et al, 2009). Finally, the participation of P450s 4F2 and 4F3B in the biotransformation of very long-chain saturated fatty acid or phytanic acid in patients with X-linked adrenoleukodystrophy (Sanders et al, 2006) or Refsum's disease (Komen and Wanders, 2006), respectively, suggests that factors that modulate CYP4F2 expression may play an important role in alleviating these diseases and possibly other disorders of lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…More recent work in which use was made of specific inhibitors has shown that members of the CYP family 4 are responsible for phytanic acid ω-hydroxylation. Incubations with microsomes containing human recombinant CYPs (supersomes) revealed that multiple CYP enzymes of the family 4 class are able to ω-hydroxylate phytanic acid with the following order of efficiency: CYP4F3A>CYP4F3B>CYP4F2>CYP4A11 [35].…”
Section: Phytanic Acid ω-Oxidation An Alternative Mechanism To Degramentioning
confidence: 99%